Differential expression profiles of long noncoding RNAs in synchronous multiple and solitary primary esophageal squamous cell carcinomas: A microarray analysis. Issue 2 (15th October 2018) - Li, Qi‐Wen; Ma, Li; Qiu, Bo; Yang, Hong; Zhu, Yu‐Jia; Qiang, Meng‐Yun; Liu, Song‐Ran; Chen, Nai‐Bin; Guo, Jin‐Yu; Cai, Ling‐Zhi; Wang, Jun‐Ye; Zhang, Xu; et al.
Abstract: As a unique subtype of esophageal cancer, synchronous multiple primary esophageal squamous cell carcinomas (ESCCs) mostly occur in Asian patients with alcohol and/or tobacco abuse, or with a family history of cancer. Multiple ESCCs are associated with poor clinical outcomes. Growing evidence has addressed that long noncoding RNAs (lncRNAs) are involved in the carcinogenesis of various malignancies. We compared the lncRNA and messenger RNA (mRNA) profiles between solitary and multiple ESCC tissues through microarray analysis, aiming at studying their different mechanisms in tumor development. As a result, in multiple ESCCs, a total of 5257 lncRNAs and 3371 mRNAs were consistently differentially expressed compared with solitary ESCC, including 2986 upregulated and 2271 downregulated lncRNAs, and 2313 upregulated, and 1058 downregulated mRNAs. We validated the results in four differentially expressed lncRNAs using quantitative real‐time polymerase chain reaction. There were 38 and 20 pathways significantly related to up‐ and downregulated transcripts. The pathways associated with mostly enriched up‐ and downregulated mRNAs were hsa01200 (carbon metabolism) and hsa05221 (acute myeloid leukemia‐ homo sapiens [human]). Gene ontology analysis suggested that upregulated and downregulated mRNAs were mainly enriched in bounding membrane of organelle involved in the cellular component and positive regulation of transport involved in the biological process. Further analysis identified 189 differentially expressed paired antisense lncRNAs and relative sense mRNA, as well as 2134 differentially expressed long intergenic noncoding RNAs and their adjacent mRNA pairs. In conclusion, the aberrantly expressed lncRNAs might play a role in the carcinogenesis of multiple ESCCs and could be candidates as diagnostic biomarkers and therapeutic targets. Abstract : We aimed to investigate the potential role of long noncoding RNAs (lncRNAs) in the development of multiple esophageal squamous cell carcinomas (ESCCs). The genome‐wide expression profiles of both lncRNAs and messenger RNA (mRNAs) between tissues from solitary and multiple ESCCs were examined. Numerous differentially expressed lncRNAs and mRNAs were identified in this study and might be used for future determination of diagnostic biomarkers and therapeutic targets.